CDNH Portal - Mihova, Marija; Jovanov, Mile; Ackovska, Nevena; Markovski, Smile (Institute of Informatics, Faculty of Natural Sciences and Mathematics, Ss. Cyril and Methodius University in Skopje, Macedonia, 2008)
The Digitization of national heritage is a process concerning several aspects. One very important aspect is the digital presentation of the cultural heritage elements. The main role of the Center for Digitization of National Heritage (CDNH) at the Institute of Informatics is to produce such presentations and put them available on the web, trough the portal of CDNH. In this paper we present the content of the CDNH portal and its structure.
Keywords: digitization, CDNH Macedonia, national heritage presentation